Repurposing Azithromycin and Rifampicin Against Gram-Negative Pathogens by Combination With Peptidomimetics - Baker, Kristin R.; Jana, Bimal; Hansen, Anna Mette; Nielsen, Hanne Mørck; Franzyk, Henrik; Guardabassi, Luca (Frontiers in Cellular and Infection Microbiology, 2019)
Synthetic peptidomimetics may be designed to mimic functions of antimicrobial peptides, including potentiation of antibiotics, yet possessing improved pharmacological properties. Pairwise screening of 42 synthetic peptidomimetics combined with the antibiotics azithromycin and rifampicin in multidrug-resistant (MDR) Escherichia coli ST131 and Klebsiella pneumoniae ST258 led to identification of two subclasses of α-peptide/β-peptoid hybrids that display synergy with azithromycin and rifampicin (fractional inhibitory concentration indexes of 0.03–0.38). Further screening of the best three peptidomimetics in combination with a panel of 21 additional antibiotics led to identification of peptidomimetics that potentiated ticarcillin/clavulanate and erythromycin against E. coli, and clindamycin against K. pneumoniae. The study of six peptidomimetics was extended to Pseudomonas aeruginosa, confirming synergy with antibiotics for five of them. The most promising compound, H-(Lys-βNPhe)8-NH2, exerted only a minor effect on the viability of mammalian cells (EC50 ≥ 124–210 μM), and thus exhibited the highest selectivity toward bacteria. This compound also synergized with rifampicin and azithromycin at sub-micromolar concentrations (0.25–0.5 μM), thereby inducing susceptibility to these antibiotics at clinically relevant concentrations in clinical MDR isolates. This peptidomimetic lead and its analogs constitute promising candidates for efficient repurposing of rifampicin and azithromycin against Gram-negative pathogens.